A Mediation Model on How Conspiracy Beliefs Concerning the Corona-Crisis Are Related to Corona-Related Behaviours - Dijkstra, Arie (Frontiers in Psychology, 2021)
Background. The endorsement of Conspiracy Beliefs concerning corona (CBc) may make people reject information from the general media, leading them to not follow recommendations on prevention behaviours, getting tested and getting vaccinated. The aim of the present study is to understand the relationship between CBc and engaging in these corona-related behaviours. Method. Two samples of participants (N=1004 and N=159) were recruited independently. Participants filled in a survey that assessed four indicators of the three behaviours, four general psychological determinants (e.g., seriousness of covid-19), five behaviour-specific psychological determinants (e.g., test reliability, vaccine effectiveness), and CBc. Results. The explained variances of the different models with regard to the four indicators of behaviour ranged from 3.9% to 75%. Mediation analyses using Hayes PROCESS model 4 showed significant mediation by general determinants in both samples, and mediation by several behaviour-specific determinants in one sample. Discussion. CBc may lead to rejection of general media information, and this may lead to states of psychological determinants that do not stimulate to engage in prevention behaviours, testing or vaccination. The present study sheds some light on how CBc can be related to corona-related behaviours.